Simulated deep space exposure on seeds utilizing the MISSE flight facility - Jeffrey T. Richards; Todd E. Mortenson; Cory J. Spern; Timothy A. Mousseau; Jennifer L. Gooden; Lashelle E. Spencer; Christina L. Khodadad; Jason A. Fischer; Alexander D. Meyers; Chad K. Papenfuhs; Jeffrey G. Buell; Howard G. Levine; et al. (npj Microgravity)
Abstract The MISSE-Seed project was designed to investigate the effects of space exposure on seed quality and storage. The project tested the Multipurpose Materials International Space Station Experiment—Flight Facility (MISSE-FF) hardware as a platform for exposing biological samples to the space environment outside the International Space Station (ISS). Furthermore, it evaluated the capability of a newly designed passive sample containment canister as a suitable exposure unit for biological samples for preserving their vigor while exposing to the space environment to study multi-stressor effects. The experiment was launched to the ISS on Northrup Grumman (NG)-15. The exposure lasted eight months outside the ISS in the MISSE-FF at the Zenith position. The specimens consisted of eleven seed varieties. Temperature dataloggers and thermoluminescent dosimeters were included in each container to record environmental data. We presented here the hardware and experimental design, environmental profiles, and seed survival from post-flight germination tests.